2014
DOI: 10.1007/s13197-014-1647-5
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling to study influence of porosity on apple and potato during dehydration

Abstract: Several structural and physical changes in foodstuffs are the consequence of water removal during the drying process. Porosity (volume fraction of pores) is one of the key parameter that affects the quality and other properties of foods (such as apple and potato). To understand the effect of dehydration in apple and potato, in the present study an arbitrary small cubic volume element is considered which contains pores (intracellular spaces) distributed in it. Further, it is assumed that each pore in the cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Modeling the osmotic process for mangoes is more complicated due to its tissue structure. Mangoes are dense and much less porous (porosity = 0.04 to 0.05) than most fruits (pineapple porosity = 0.16 to 0.25; apple porosity = 0.18 to 0.22; strawberry porosity = 0.47) (Ozcan and Haciseferogullan 2007;Yan et al 2008;Singh et al 2015). This tissue structure imposes a higher resistance to mass transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Modeling the osmotic process for mangoes is more complicated due to its tissue structure. Mangoes are dense and much less porous (porosity = 0.04 to 0.05) than most fruits (pineapple porosity = 0.16 to 0.25; apple porosity = 0.18 to 0.22; strawberry porosity = 0.47) (Ozcan and Haciseferogullan 2007;Yan et al 2008;Singh et al 2015). This tissue structure imposes a higher resistance to mass transfer.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on dried apple and potato also showed that forced convective drying resulted in products with a higher (Eulerian) porosity. [59][60][61] Using a Lagrangian approach, we nd that the pore volume stays almost constant for our forced convective condition. This is due to a small degree of bulk shrinkage while cells shrink during drying.…”
Section: Discussionmentioning
confidence: 96%
“…The high porosity of freeze-dried food is created as an effect of the absence of capillary forces during sublimation of the frozen water [92]. A similar value was obtained for freeze-dried gels with a combination of xanthan gum and locust bean gum [84,85], freeze-dried apple and potato [93]. In the case of freeze-dried strawberry gels, the porosity was in the range of ~88-91% [94].…”
Section: Properties Of Dried Gels and The Effect Of Different Ingredimentioning
confidence: 82%